2015
DOI: 10.3153/jaefr15019
|View full text |Cite
|
Sign up to set email alerts
|

SOME VARIETIES OF PATHOLOGICAL CHANGES IN EXPERIMENTAL INFECTION OF CARPS (Cyprinus carpio) WITH Aeromonas hydrophila

Abstract: Abstract:The main clinical and pathomorphological changes in Aeromonas hydrophila infection in carp provoked by different field strains of this bacterium were studied. The strongest histopathological damages were seen in the functional epithelium of liver and kidneys, followed by intestine and hearth damages in addition to various haemorrhages in interstitial tissues of visceral organs and some skin haemorrhages on the ventral surface of the body and the anal region. As a whole, pathological damages consisted … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
15
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 26 publications
(20 citation statements)
references
References 21 publications
5
15
0
Order By: Relevance
“…Our findings were much similar to the symptoms found in other fish species (Abdelhamed et al, 2017, Alsaphar and Al-Faragi, 2012, Cipriano et al, 1984, Khamees et al, 2013, Kumar et al, 2016, Stratev et al, 2015). Many studies showed that the chronic infections of A .…”
Section: Resultssupporting
confidence: 91%
See 2 more Smart Citations
“…Our findings were much similar to the symptoms found in other fish species (Abdelhamed et al, 2017, Alsaphar and Al-Faragi, 2012, Cipriano et al, 1984, Khamees et al, 2013, Kumar et al, 2016, Stratev et al, 2015). Many studies showed that the chronic infections of A .…”
Section: Resultssupporting
confidence: 91%
“…It can cause local pathology to the host tissue. The host’s reaction may be in the form of tissue proliferation, degeneration and inflammation (Stratev et al, 2015). A. hydrophila can be a pathogenic agent not only for fish, amphibians and reptiles, but also for mammals, including humans (Aoki, 1999, Janda and Abbott, 2010, Lallier and Higgins, 1988, Plumb and Hanson, 2011, Stratev et al, 2015, Trott, 2006).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…These pigmented cells may appear isolated or in the form of a cluster where it indicates the positive presence of neutral carbohydrate and melanin (Agius & Roberts, ). Our results were much like the findings found in other fish species in previous investigations (Abdelhamed, Ibrahim, Baumgartner, Lawrence, & Karsi, ; Brenden & Huizinga, ; Cipriano, Bullock, & Pyle, ; Kumar et al, ; Stratev, Stoev, Vashin, & Daskalov, ).…”
Section: Discussionsupporting
confidence: 92%
“…Moreover, various haemorrhagic patches were found in the interstitial tissue of the visceral organs, anal region and on the ventral surface of the body. It has been proposed that several virulence factors derived from A. hydrophila contribute significantly to the discussion of the pathogenesis of infection by this organism (Stratev et al, ). Many Aeromonas sp.…”
Section: Discussionmentioning
confidence: 99%